2019
DOI: 10.1177/0022219419856013
|View full text |Cite
|
Sign up to set email alerts
|

Improving Teachers’ Comprehension of Curriculum-Based Measurement Progress-Monitoring Graphs

Abstract: The authors examined three instructional approaches for improving teachers’ curriculum-based measurement (CBM) graph comprehension, each differing in the extent to which reading the data, interpreting the data, and linking the data to instruction were emphasized. Participants were 164 elementary school teachers who were randomly assigned to one of three CBM instructional approaches or a control condition. Instruction was delivered via videos. Prior to and after receiving instruction, teachers completed a CBM g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…As Gotch and McLean (2019) found, PD increased teacher confidence, but had no impact on their assessment knowledge, which we also found. In addition, our finding that training had no effect on teacher knowledge was supported by prior research (Coburn & Turner, 2011; Newell & Christ, 2017) and, again, is contradicted by others (van den Bosch et al, 2019). One key issue for researchers to examine further is what format and dosage of PD is most beneficial for teachers.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…As Gotch and McLean (2019) found, PD increased teacher confidence, but had no impact on their assessment knowledge, which we also found. In addition, our finding that training had no effect on teacher knowledge was supported by prior research (Coburn & Turner, 2011; Newell & Christ, 2017) and, again, is contradicted by others (van den Bosch et al, 2019). One key issue for researchers to examine further is what format and dosage of PD is most beneficial for teachers.…”
Section: Discussionsupporting
confidence: 48%
“…It is reasonable to assume that teachers with more PD will become more knowledgeable and, indeed, studies have found the positive influence that PD has on assessment and data-use knowledge (Coburn & Turner, 2011; Lukin et al, 2004; van den Bosch et al, 2019). Unfortunately, increased knowledge resulting from PD does not necessarily ensure an increase in data use (Randel et al, 2016).…”
Section: Pdmentioning
confidence: 99%
“…Most treatment conditions included opportunities for applied practice across days ( n = 38; 80.85%); CBM software that automatically graphed data, applied decision rules, and provided reports of student progress ( n = 27; 57.45%); and individual student CBM reports ( n = 40; 85.10%). Researchers in two studies (four conditions) included technology to train teachers (i.e., content acquisition podcasts in Kennedy et al, 2016; digital modules in van den Bosch et al, 2019). For each treatment condition, researchers used one or more additional report component or support.…”
Section: Resultsmentioning
confidence: 99%
“…For each QI, authors needed to report information required by the QI to receive credit. The 28 included studies met an average of 88.77% ( SD = 7.09; range: 66.67%–100%) of the applicable QIs, with two studies (McMaster et al, 2020; van den Bosch et al, 2019) meeting 100% of the indicators. All 28 studies met 10 of the QIs, if the QI was applicable (QI 1.1, 4.2, 6.1, 6.3, 6.8, 7.1, 7.2, 7.4, 7.6, 8.1).…”
Section: Resultsmentioning
confidence: 99%
“…Supporting this argument, van Kuijk et al (2016) demonstrated that professional development that targeted teachers’ goal-setting, data use, and instruction led to improvements in their students’ reading comprehension. Specific to CBM, van den Bosch et al (2019) found that directed, guided instruction in CBM graph comprehension led to improvements in teachers’ ability to interpret CBM data and link it to instruction; however, the authors questioned the extent to which such instruction was typically included in CBM professional development training.…”
Section: Teachers Do Not Receive Sufficient Instruction On the Data-based Decision-making Aspects Of Cbmmentioning
confidence: 99%